Mechanical Splices for Seismic Retrofitting of Concrete Structures - Huaco, G. (2020)
As an alternative to lap splicing, mechanical splices can be used for retrofit purposes. They are generally most economical than traditional lap splices when available spacing or length makes laps difficult to utilize. Mechanical splices are frequently used in new construction. However, their use is limited and not practical for use in retrofitted structures. However, if the bars to be joined do not need to be threaded in order to be connected with a special mechanical splice, such mechanical splices can be useful. It is presented a proposal of using two types of mechanical splices for retrofit purposes. Cycle Tension and cycle tension-compression tests are presented and discussed. It was found that mechanical splices are suitable and have acceptable response under seismic loads.